Effects of Ramadan fasting on the diurnal variations of physical and cognitive performances at rest and after exercise in professional football players - Khemila, Syrine; Romdhani, Mohamed; Farjallah, Mohamed Amine; Abid, Rihab; Bentouati, Emna; Souissi, Mohamed Abdelkader; Abedelmalek, Salma; Garbarino, Sergio; Souissi, Nizar (Frontiers in Psychology, 2023)
Introduction Ramadan fasting (RF) is characterized by daily abstinence from food and fluid intake from dawn to sunset. The understanding of the Ramadan effects on the diurnal variations of athletic and cognitive performance is crucial for practitioners, coach and researchers to prepare sport events and optimize performance. The aim of the present study was to reveal the effects of RF on the diurnal variation of physical and cognitive performances at rest and after exercise. Method In a randomized order, 11 male football players (age: 19.27 ± 0.9; height: 1.79 ± 0.04 cm; body mass: 70.49 ± 3.97 kg; BMI: 21.81 ± 1.59 kg/m2) completed a 30-s Wingate test [i.e., mean (MP) and peak powers (PP)] at 07:00, 17:00, and 21:00 h on five occasions: 1 week before Ramadan (BR); the second (R2); the third (R3); the fourth (R4) week of Ramadan; and 2 weeks after Ramadan (AR), with an in-between recovery period of ≥72 h. Simple (SRT) and choice (CRT) reaction times, mental rotation test (MRT) and selective attention (SA) test were measured before and after Wingate test. Rating of perceived exertion (RPE), body composition, dietary intake, profile of mood states (POMS) and Pittsburgh Sleep Quality Index (PSQI) were assessed over the five periods. Results Compared to BR, RF decreased MP at 17:00 h (p < 0.05, d = 1.18; p < 0.001, d = 2.21, respectively) and PP at 17:00 h (p < 0.05, d = 1.14; p < 0.001, d = 1.77, respectively) and 21:00 h (p < 0.01, d = 1.30; p < 0.001, d = 2.05, respectively) at R3 and R4. SRT (p < 0.001,d = 1.15; d = 1.32, respectively), number of correct answers (MRTE; p < 0.05, d = 1.27; d = 1.38, respectively) and SA (p < 0.01, d = 1.32; d = 1.64, respectively) increased during R2 and R3 in the evening before exercise compared to BR. Short term maximal exercise enhanced SRT (p < 0.01, d = 1.15; p < 0.001, d = 1.35, respectively), MRTE (p < 0.001, d = 2.01; d = 2.75 respectively) and SA (p < 0.05, d = 0.68; d = 1.18, respectively) during R2 and R3 in the evening. In comparison to BR, sleep latency and sleep duration increased during R3 (p < 0.001, d = 1.29; d = 1.74, respectively) and R4 (p < 0.001, d = 1.78; d = 2.19, respectively) and sleep quality increased in R2, R3 and R4 (p < 0.01, d = 1.60; p < 0.001, d = 1.93; d = 2.03, respectively). Conclusion During RF, anaerobic and cognitive performances were unaffected in the morning but were impaired in the afternoon and evening. Short-term maximal exercise mitigates the negative effects of fasting on cognitive performance. Maximal exercise could thus partially counteract the effect of fasting on cognitive function.